'Not Taking, but Giving': A Paradox of Cross-Cultural Empowerment - Scott, Kim; Durey, Angela (Springer Verlag, 2014)
This chapter examines the nature of partnerships between mining companiesand Aboriginal and Torres Strait Islander communities in regional WesternAustralia from the perspective of Indigenous health, well-being and culture. Referencewill be made to specific examples of such partnerships, and attention drawnto research indicating a correlation between the health and well-being of Indigenouspeople, and their connection to traditional culture along with ‘self-determination’.The impetus Native Title legislation has given to promoting dialogue, collaborationand negotiation between the mining industry and Indigenous communities will beconsidered, along with an apparent readiness by the mining industry to be moresupportive generally of Indigenous culture and its place in mainstream Australia.The chapter will focus particularly on the participation of Indigenous individuals inthe mining workforce and related business opportunities, the role and potential ofcultural awareness training supplied by Indigenous communities to the miningindustry and suggestions as to future directions.